ONE YEAR REVIEW OF PATIENTS ADMITTED WITH CARDIAC DISEASES IN PREGNANCY IN A TERTIARY CARE HOSPITAL OF PESHAWAR - Hussain, Shahzadi Saima; Shafqat, Tanveer; Raees, Mehnaz; Qazi, Qudsia (Journal of Postgraduate Medical Institute, 2021)
Objective: To identify the frequency and type of cardiac diseases in pregnant women and their fetal and maternal outcome. Methodology: This observational study was carried out in Unit A, Department of Gynecology and Obstetrics, Lady Reading Hospital, Peshawar from mid January 2019 to mid January 2020. After informed written consent, using non probability consecutive sampling all pregnant women presenting with cardiac diseases were included in this study. Age, parity, mode of delivery, and period of gestation were recorded. Cardiac disease was diagnosed on the basis of symptoms, ECG and echocardiography. Types of different cardiac lesions and maternal risk were noted according to Modified World Health Organization classification of maternal cardiovascular risk. Maternal and fetal outcomes were measured in terms of mortality. Data was analyzed using SPSS version 20. Results: In one year, a total of 10263 pregnant ladies were admitted and among them 43 (0.42%) patients had cardiac disease. It was observed that 79.1% (n=35) were diagnosed for 1st time during pregnancy. Most frequent cardiac disorder was cardiomyopathy, found in 27.9% (n=12) of patients, followed by congenital heart disease in 18.6% (n=8), in the form of mitral and aortic stenosis. Maternal and fetal mortality was 4.7% (n=2) and 9.3% (n=4), respectively. Conclusion: There is a small proportion of pregnant patients with cardiac disease among all pregnancies. Most of the patients were multiparous and cardiomyopathy was found to be the most prevalent cardiac disease.